HUBUNGAN ANTARA KESUNGGUHAN (CONSCIENTIOUSNESS) DENGAN HASIL BELAJAR BIOLOGI: STUDI KORELASIONAL TERHADAP SISWA KELAS X MIPA DI SMA NEGERI 38 JAKARTA - Mieke Miarsyah; Melani Wulandari; I Made Putrawan (Universitas Negeri Jakarta, 2016)
Conscientiousness is exhibited by those who described asdependable, organized, through and responsible. The lack of students conscientiousness make their study result on ecosystem learning of Biology subject became low. This study aims to determine correlation between conscientiousness and study result of biology students at the 38 Senior High School Jakarta in ecosystem subject. This research was held in January-February 2016. The method was used a survey method through correlative studies. The samples were 105 students from Mathematic and Science first grade. The results of normality and homogeneity test showed that data come from normal distribution of populations and homogeneous. The results of hypothesis test showed that there was significant positive correlation between conscientiousness and study result of biology students with a correlation coefficient 0,804 in the equation Å¶ = 5.663 + 0.195X. Conscientiousness contribute to study result of Biology students amounted to 64,69%.